Age and postoperative opioid use in women undergoing pelvic organ prolapse surgery - Shannon Cummings; Natalie V. Scime; Erin A. Brennand (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Our objective was to explore the relation between patient age and postoperative opioid use up to 24 hours following pelvic organ prolapse (POP) surgery. Material and methods We conducted a prospective cohort study following 335 women ranging in age from 26 to 82 years who underwent surgery for multi‐compartment POP at a tertiary center in Alberta, Canada. Patient characteristics were measured using baseline questionnaires. Perioperative data were collected from medical chart review during and up to 24 hours following surgery. We used logistic regression to analyze the odds of being opioid‐free and linear regression to analyze mean differences in opioid dose, measured as total morphine equivalent daily dose, exploring for a potential non‐linear effect of age. Adjusted models controlled for preoperative pain, surgical characteristics and patient health factors. Results Overall, age was positively associated with greater odds of being opioid‐free in the first 24 hours after surgery (adjusted odds ratio per increasing year of age = 1.07, 95% confidence interval [CI] 1.04–1.09, n = 332 women). Among opioid users, age was inversely associated with total opioid dose (adjusted mean difference per increasing year of age = 0.71 mg morphine equivalent daily dose, 95% CI −0.99 to −0.44, n = 204 women). There was no evidence of a non‐linear relation between age and postoperative opioid use or dose. Conclusions In the context of POP surgery, we found that younger women were more likely to use opioids after surgery and to use a higher dose in the first 24 hours when compared with older women. These findings support physicians to consider age when counseling POP patients regarding pain management after surgery, and to direct resources aimed at opioid‐free pain control towards younger patients.